DEVELOPING CofiD-20 GAME FOR TEACHING READING COMPREHENSION TO THE TENTH GRADE STUDENT: RESEARCH AND DEVELOPMENT - Yudhi Irawan; Supriyono; Adin Fauzi (Universitas Islam Balitar, 2022)
The purpose of this study was to determine the game as a medium for learning reading comprehension that focuses on descriptive text, to determine English reading skills for learning reading comprehension, and to determine the ability of teachers and students' responses to the use of these media for learning reading comprehension in high school. The researcher adapted Sugiyono's research and development framework as a research reference. Adaptation is formulated in three phases, namely: basic research; design and development; and perception and finalization tests. The results showed that the game-based learning media had been validated by media and material experts and the responses of teachers and students had been carried out. The results of media experts 88.5% are included in the